Complexos de rutênio(ii) contendo fármacos anti-inflamatórios: síntese, caracterização e estudo da atividade citotóxica - Lopes, Junai Carvalho de Souza (2015)
This work describes the synthesis and characterization of five new ruthenium(II) complexes with three biologically active ligands: the anions of diclofenac, ibuprofen and naproxen. These complexes have the general formula cis-[Ru(O-O)(P-P)2]PF6 where P-P = dppm or dppe, and (O-O) = anion of diclofenac, ibuprofen or naproxen. All isolated compounds were characterized by elemental analysis, vibrational spectroscopy in the infrared region, absorption spectroscopy in the ultraviolet visible region and 31P{1H} nuclear magnetic resonance. The structure of cis-[Ru(ibu)(dppm)2]PF6 complex was determined by monocrystal X-ray diffraction confirming that all the ligands are coordinated in a bidentate fashion to the Ru(II) ion. The cis-[Ru(dicl)(dppm)2]PF6 and cis-[Ru(ibu)(dppm)2]PF6 complexes were evaluated according to their cytotoxic capacity against to human cancer cells lines HepG2 (hepatocellular carcinoma), MCF-7 (breast adenocarcinoma), MO59J (glioblastoma) and normal human cell line GM07492A (lung fibroblast). The results showed significant increase in cytotoxic activity when compared to the precursor complex and improved activity relative to the cisplatin, for the MO59J cell line. The cis-[Ru(ibu)(dppm)2]PF6 complex displayed higher a activity in all performed tests. Although, these complexes showed no selectiveness when confronted with normal cells.